IMPACT OF BACTERIAL KERATITIS ON OUTPUT CARE HOSPITAL IN BANGLADESH - Reza, Mohammed Selim; Miah, Md Rahimullah; Islam, Nazmul; Silvy, Jafrin Sultana; Hussain, Nizam Jamil; Parisha, Jorin Tasnim; Jhuma, Azima Aktar; Hossain, Md Altaf; Rashid, Md Harunur; Chowdhury, Shahriar Hussain (International Journal of Research -GRANTHAALAYAH, 2025)
Background Bacterial keratitis is a potentially fatal corneal infection worldwide. Its deleterious effects include sudden and rapid destruction of the cornea. The exact cause is still unknown to health authorities and ophthalmologists. Various studies have suggested different theories. Some studies have suggested that the spectrum of bacterial corneal pathogens is largely influenced by local microbial flora, geography, and climatic factors. Aims and Objectives The aim of this study is to determine the bacteriological patterns and predisposing factors of bacterial keratitis in outpatient settings. Methods A total of 45 male and female patients with bacterial keratitis were evaluated from January 2015 to December 2016 at the Department of Ophthalmology, MAG Osmani Medical College Hospital, Sylhet, a divisional city of Bangladesh. The study recorded the patients' socio-demographic information, pre-existing factors, and clinical presentation. Bacterial cultures were performed from corneal swabs in the laboratory. Results The age range of most patients was between 41 and 60 years (55.6%). The mean age of bacterial keratitis was 47.60 ± 17.14 (range, 18–71) years. The study showed that the male to female ratio was 1.25:1, which was close to 1. The study also showed that common predisposing factors were 62.2% trauma and 31.1% chronic dacryocystitis. The highest 57.8% Gram-positive bacteria predominated, and the lowest 42.2% Gram-negative bacteria. Out of the total isolates, 37.8% were Staphylococcus epidermidis, 26.7% Pseudomonas aeruginosa, 20.0% Staphylococcus aureus, 8.9% Escherichia coli, and 6.7% Klebsiella species. Conclusion The study concluded that trauma is the most important predisposing factor in bacterial keratitis. Gram-positive bacteria are the main isolates and common bacteria are Staphylococcus epidermidis, Pseudomonas aeruginosa and Staphylococcus aureus. This study suggests a new dynamic alternative approach to the upcoming eye care pathway to promote global eye protection related to advanced sensor technology and national health policies, which is aligned with the Sustainable Development Goals 2030.